1992
DOI: 10.1128/jvi.66.3.1520-1527.1992
|View full text |Cite
|
Sign up to set email alerts
|

Association of heat shock protein 70 with enterovirus capsid precursor P1 in infected human cells

Abstract: Members of the human heat shock (HSP) family of related proteins are involved in the intracellular folding, transport, and assembly of proteins and protein complexes. We have observed that human heat shock protein 70 (HSP70) is associated with the capsid precursor P1 of poliovirus and coxsackievirus Bi in infected HeLa cells. Antiserum generated against HSP70 coimmunoprecipitated the poliovirus protein P1, an intermediate in capsid assembly. Similarly, a-virion serum coimmunoprecipitated HSP70 from virus-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…In this study, we identified two molecular chaperones incorporated into purified NDV particles, HSP70 and HSP90. HSP70 interacts with various viral proteins and may be involved in the assembly of adenovirus [41], enterovirus [42], vaccinia virus [43] and hantaan virus [44]. Virion-associated HSP70 might participate in early events of infection, uncoating the viral capsid in a manner similar to its role in the uncoating of clathrin cages [65].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified two molecular chaperones incorporated into purified NDV particles, HSP70 and HSP90. HSP70 interacts with various viral proteins and may be involved in the assembly of adenovirus [41], enterovirus [42], vaccinia virus [43] and hantaan virus [44]. Virion-associated HSP70 might participate in early events of infection, uncoating the viral capsid in a manner similar to its role in the uncoating of clathrin cages [65].…”
Section: Discussionmentioning
confidence: 99%
“…3C and 5, we propose that the newly made capsid precursor P1 that is released from the polyprotein and myristoylated ( Fig. 3C, PV stage I) interacts with the chaperone Hsp90 to achieve a conformation (PV stage II) competent for cleavage by 3CD pro (33,34). After proteolytic processing, assembly of the cleavage products occurs in a stepwise manner.…”
Section: Model Of Enterovirus Morphogenesismentioning
confidence: 97%
“…The N-terminal glycine of the newly formed poliovirus P1 capsid precursor is rapidly modified (perhaps also cotranslationally) by covalent linkage to myristic acid (30)(31)(32), after which it becomes a client of the cellular chaperone Hsp90 to attain a processing-competent conformation (referred to as P1* in Fig. 3C, step II) (33,34). It is not known whether myristoylation of PV P1 is a prerequisite for its interaction with the chaperone Hsp90.…”
Section: Figmentioning
confidence: 99%
“…HSP70 and HSP90 have been found incorporated into IBV. HSP70 interacts with various viral proteins and may be involved in the assembly of adenovirus [45], enterovirus [46], vaccinia virus [47] and hantaan virus [48]. Alternatively, upon entry into susceptible target cells, virion-associated HSP70 might participate in early events of infection.…”
Section: Discussionmentioning
confidence: 99%